(untitled) (Alternautas, 2023)
Buenos Aires is globally appealing for its diverse culture, history, and opportunities. It lures people for employment, education, and healthcare, adding to urbanization tensions. The city administration advertises integrative urbanism to improve attractiveness but struggles with high crime rates, particularly compared to some European cities. This study focuses on safety through a feminist urbanism lens. We question the effectiveness of safety measures and who benefits from them. Key considerations include how various demographics, from the elderly to security forces, perceive safety and city renovations. We adopt a feminist perspective, referencing seminal works like Leslie Kern’s ’Feminist City’ (2021) and Argentine activist Ana Falú (2022). Utilizing participatory mapping tools designed in Latin America, our study aims to decolonize traditional knowledge production methods.